Instytucja kościoła: wspólnota wartości czy grupa interesu? - Dylus, Aniela (The institution of church: a community of values or a group of interest?, 2005)
The article considers a question - whether Church is a group of interest, and if this is the case, what kind of group it belongs to. This question is rarely brought up directly. Rare statements on this subject given by sociologists, economists, philosophers, ethics teachers and lawyers, usually formulated as of secondary importance, demonstrate a significant divergence of opinions. We can divide them into the following types: Church is one of many groups of interest, Church is a particular group of interest, Church is not a group of interest. If one reduces Church to a group of interest, it is regarded as public, extraeconomic and of considerable size. It demonstrates the features which can classify the group both as inclusive and exclusive group of interest. Consequently, the legal status of Church especially in relation to State ranges from a system of State church through a system of complete separation between Church and State till the system of moderate separation between the two. Searching the explanation of this pluralism, it is worth formulating two hypotheses: 1. Inserting Church into the practice and theory of group behaviour or excluding it from this area is historically and culturally conditioned. Negative experience of individuals or whole societies both local and national ones which were connected with Church or anti-secularity of church people show the tendency to classify Church as a one of numerous groups of interest, fighting for special privileges for its own organization. The processes of secularization are also very favourable context for the reduction of Church to a group of interest. 2. Deeply rooted reasons for regarding Church as a group of interest should be understood in terms of accepting or refusing the premises about the interest-oriented human nature and the whole society. The utilitarian a priori in philosophical anthropology, in social and political philosophy, finds its reflection in "interest-oriented" identification of Church. The final conclusion of the presented considerations, implying that the institution of Church is not a group of interest, is based on accepting indeterministic premise of understanding social reality. It does not mean that a historical presence of Church in the society cannot take the typical for a group of interest character.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1090, s. 96-108